The Mindful Compassion Program Integrated with Body-Mind-Spirit Empowerment for Reducing Depression in Lung Cancer Patient-Caregiver Dyads - Fei-Hsiu Hsiao; Chao-Chi Ho; Chong-Jen Yu; Jin-Yuan Shih; Zhong-Zhe Lin; Feng-Ying Huang; Yu-Ting Chen; Chia-Chen Hsieh (Psychosocial Intervention)

(untitled)
Objective: This study compared the long-term effects of a mindful compassion program on improving depression in lung cancer patients, both in patient-caregiver dyads and in patient-only groups, and examined the moderating roles of anxiety and quality of life (QOL). Method: Participants consisted of 56 dyads, who were randomly assigned to either the dyadic or patient-only groups. Data collection included various assessments at different time points: baseline (T0), end of intervention (T1), and follow-up at the 5th month (T2), 8th month (T3), and 14th month (T4). Results: Patients in the dyadic group experienced a significant reduction in depressive symptoms. The dyadic intervention was particularly beneficial for younger patients and those with higher baseline QOL symptom distress. Improvements in patients’ mindfulness and self-compassion contributed to reduced depression by enhancing general health and lowering anxiety. Additionally, caregivers’ self-compassion played a role in reducing patients’ depression by improving patients’ QOL functioning and decreasing anxiety. Conclusions: Mindfulness and compassion interventions, whether provided dyadically or individually, can be tailored to each patient’s specific condition.